The Effect of Realistic Mathematics Education Approach to Improve Students' Mathematics Learning Outcomes - Zetriuslita, Zetriuslita; Andrian, Dedek; Suripah, Suripah; Maimunah, Maimunah; Hidayat, Riyan; Dacara, Editha (Jurnal Riset Pendidikan Matematika, 2025)
Learning outcomes are influenced by the process carried out during learning. The learning process is carried out by applying innovative learning models/approaches.This study aims to determine the effect of the Realistic Mathematics Education (RME) approach on the mathematics learning outcomes of grade VIII students at Siak Hulu Junior High School. Employing a development research design combined with a pseudo-experimental methodology, the research involved a population of six classes (VIII1 to VIII6). A purposive sampling technique was utilized, resulting in two selected classes: VIII3, comprising 32 students as the control group, and VIII4, also with 32 students, serving as the experimental group. The development phase produced a valid and practical student worksheet designed to facilitate the RME approach. The findings indicated that students who engaged with the RME approach demonstrated significantly better mathematics learning outcomes compared to those who experienced conventional teaching methods. Statistical analysis confirmed the effectiveness of the RME approach, suggesting that it not only enhances understanding but also improves overall performance in mathematics. This study concludes that the implementation of the RME approach positively influences the mathematics learning outcomes of grade VIII students in SMP 6 Kampar Regency, highlighting its potential as an effective pedagogical strategy in mathematics education. The research contributes to providing evidence for the adoption of realistic approaches in classroom settings to foster improved student engagement and achievement in mathematics. Recommendations for teachers to be encouraged to develop media and teaching materials that are contextualised and relevant to students' daily lives likes Trigonometry subject